2018
DOI: 10.3390/mi9020067
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Single-Molecule Junctions Based on Current–Voltage Characteristics

Abstract: The relationship between the current through an electronic device and the voltage across its terminals is a current–voltage characteristic (I–V) that determine basic device performance. Currently, I–V measurement on a single-molecule scale can be performed using break junction technique, where a single molecule junction can be prepared by trapping a single molecule into a nanogap between metal electrodes. The single-molecule I–Vs provide not only the device performance, but also reflect information on energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Reviews on the experimental features and modelling approaches can be found in ref. 155 and ref. 156 , respectively.…”
Section: Box 1 | Vibronic Effectsmentioning
confidence: 86%
“…Reviews on the experimental features and modelling approaches can be found in ref. 155 and ref. 156 , respectively.…”
Section: Box 1 | Vibronic Effectsmentioning
confidence: 86%
“…Though this appears a large oversimplification, the model enjoys a wide applicability; by tuning the magnitude of , one can emulate a variety of junctions [ 26 ], from almost insulating molecular junctions with to highly conductive junctions of metal atoms where . The model can also properly describe non-linear I – V characteristics of various molecular junctions [ 4 , 27 ]. These successes of the single-level model come from the fact that, in typical atomic and molecular junctions, only one energy level among many levels of the bridging atom/molecule gives a dominant contribution to electron transmission.…”
Section: Theoretical Calculations Of Contact Admittancementioning
confidence: 99%
“…Another group of experiments using modulated biases is an inelastic transmission spectroscopy [ 27 , 51 ] where the second derivative of the I – V curve is measured with the lock-in detection technique. The modulation frequency is typically a few kHz or lower.…”
Section: Experiments On the Admittance Of Atom-sized Contacts Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-molecular junctions have received much attention in recent decades, as they can allow for learning the properties of single molecules, especially the electron transport through single molecules [ 1 , 2 , 3 , 4 ]. Typically, single-molecular junctions are constructed with electrode, molecule, and electrode through scanning tunneling microscopy break junction (STM-BJ) [ 5 , 6 , 7 ] or mechanical controlled break junction (MCBJ) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%